Space Deixis in Kedah's Dialect: (Deiksis Reruang dalam Dialek Kedah) (Jurnal Bahasa, 2014)
This article aims to examine space deixis or place deixis in the Kedah dialect, giving focus to the research area of Kampung Kubang Lintah, in the sub-district of Lepai and Kota Setar District (DKKS). Space deixis is concerned with the specification of location in space relative to that of the participants at coding time in a speech event (Huang 2007:149). This research was conducted using recorded conversations among family members, i.e. between mother and child, and between siblings. In order to express spatial relationships between the entity to be located (referent) and the landmark, this article will employ the frames of reference proposed by Huang (2007). There are three linguistic frames of reference namely (i) intrinsic, (ii) relative, and (iii) absolute. This article reveals that DKKS contains various deictic elements in expressing the relationship between the referent and the place to be referred. Spatial relationships are also relative, based on the relationship between a viewpoint (location), referent (object) and landmark (ground). The descriptive analysis of space deixis will highlight the use of deixis in Malay dialects, particularly in the Kedah dialect, as exemplified by the participants from DKKS.Keywords: deixis, space deixis, Kedah dialect, frames of reference, participant deixis